Предмет: Алгебра,
автор: Dmitriq02
4x-3/2-5-2x/3-3x-4/3=5
Ответы
Автор ответа:
0
1) (4х-3)/2-(5-2х)/3-(3х-4)/3=5
12х-9-(10-4х)-(6х-8)/6=5
12х-9-10+4х-6х+8/6=5
10х-11/6=5 множим на 6
10х-11=30
10х=41
х=41/10=4,1
Ответ: х=4,1
ВРОДЕ ТАК)
12х-9-(10-4х)-(6х-8)/6=5
12х-9-10+4х-6х+8/6=5
10х-11/6=5 множим на 6
10х-11=30
10х=41
х=41/10=4,1
Ответ: х=4,1
ВРОДЕ ТАК)
Похожие вопросы
Предмет: Алгебра,
автор: akerkeuktemova
Предмет: Английский язык,
автор: novicki24
Предмет: Русский язык,
автор: Аноним
Предмет: Алгебра,
автор: stasy9797